Assessing genetic variation of maize (Zea mays) root DNA density under contrasting water supply. (8th November 2019) - Steinemann, Sebastian; Westermeier, Peter
Abstract: Optimizing root systems is one crucial point in drought tolerance breeding of plants. Introducing root‐related traits to breeding programmes is time‐consuming and laborious. Most of the commonly used methods are not suitable to be applied in a larger amount of plants. Here we present a study applying a DNA‐based root phenotyping method (root DNA density; RDD) for phenotyping the root system of maize. Twenty‐one maize inbred lines were investigated in a rain‐out shelter experiment and 19 maize inbred lines in a greenhouse experiment under well‐watered and drought conditions. Beside other commonly used root traits, agronomic traits of the plants were recorded and compared to RDD. Within root traits, RDD showed high significant genotypic variation and the highest repeatabilities of up to 72.4%. In contrast to most agronomic traits, repeatabilities increased under drought conditions. Values showed also good correlations between rain‐out shelter and greenhouse trial, indicating the potential of this method for obtaining comparable results across different environments.